2018
DOI: 10.31235/osf.io/fg73x
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Blood donation across the life course: the influence of life events on donor lapse

Abstract: This article examines how blood donation loyalty changes across the life course as a result of life events.Previous studies have shown that life events affect involvement in prosocial behavior, possibly as a result of loss of human and social capital. using registry data from the blood collection agency in the netherlands, linked to longitudinal survey data from the Donor InSight study (n = 20,560), we examined whether life events are related to blood donor lapse. childbirth, losing a job, and starting a job i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 11 publications
(11 reference statements)
1
17
0
Order By: Relevance
“…Why and when do people give blood? Life events related to family composition, health of family and friends, and labour market transitions affect blood donor behaviour over the life course . Longitudinal studies from Germany and the Netherlands showed such life events to impact both entry to and exit from the donor pool, hereby illustrating the importance of longitudinal data to examine behavioural change across the blood donor career.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Why and when do people give blood? Life events related to family composition, health of family and friends, and labour market transitions affect blood donor behaviour over the life course . Longitudinal studies from Germany and the Netherlands showed such life events to impact both entry to and exit from the donor pool, hereby illustrating the importance of longitudinal data to examine behavioural change across the blood donor career.…”
Section: Introductionmentioning
confidence: 82%
“…Individuals with more available time, and more human and social capital (e.g. available health and social connections) were indeed more likely to donate blood , and these mechanisms were found to partially explain the association between life events and donor lapse among Dutch donors .…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…For all included donors, we identified their first whole blood donation attempt in the period 2013 to 2015 as target donation . Donor nonreturn (or lapse, as it is often called in the literature) was defined as not returning for a new donation attempt within 2 years after the donor was eligible to donate again after the target donation. Hence, the follow‐up period was as long as the ineligibility period plus 2 years or until the end of the inclusion period (December 31, 2017).…”
Section: Methodsmentioning
confidence: 99%